INSILICO DOCKING STUDIES OF THYMOQUINONE AS POTENTIAL ANTI TUMOR DRUG TARGET - TAHSEEN ALI; SHYAMALA KATRAGADDA; JERRINE JOSEPH (International Journal of Pharma and Bio Sciences, 2015)
Conventional cancer therapies cause serious side effects and, at best, merely extend the patient’s lifespan by a few years. Cancer control may therefore benefit from the potential that resides in alternative therapies. Hence, in this insilico study, we have attempted to perform docking studies of thymoquinone and poloxime with apoptotic proteins. A Glide score of -10 or lower usually represent good binding.The results demonstrate that the probable targets if validated in wet lab may provide insight into deciphering the mechanism of action